Abnormal Expression of YAP Is Associated With Proliferation, Differentiation, Neutrophil Infiltration, and Adverse Outcome in Patients With Nasal Inverted Papilloma - Yuan, Tian; Zheng, Rui; Zhou, Xiang-min; Jin, Peng; Huang, Zhi-qun; Zi, Xiao-xue; Wu, Qing-wu; Wang, Wei-hao; Deng, Hui-yi; Kong, Wei-feng; Qiu, Hui-jun; Zhou, Sui-zi; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: Nasal inverted papilloma (NIP) is a common benign tumor. Yes-associated protein (YAP) is the core effector molecule of the Hippo pathway which regulates the proliferation and differentiation of airway epithelium. While its role in proliferation may be connected to NIP formation, no definitive association has been made between them. Methods: We compared the difference of YAP expression and proliferation level between the control inferior turbinate, NP (nasal polyps), and NIP groups. In addition, we further used PCR, immunofluorescence, and immunohistochemistry to investigate YAP’s role in the proliferation and differentiation of the nasal epithelium, and inflammatory cell infiltration, correlating them with different grades of epithelial remodeling. We further used an IL-13 remodeling condition to investigate YAP’s role in differentiation in an in vitro air-liquid interface (ALI) human nasal epithelial cell (hNECs) model. Finally, we also explored the correlation between YAP expression and clinical indicators of NIP. Results: The expression of YAP/active YAP in the NIP group was significantly higher than that in the NP group and control group. Moreover, within the NIP group, the higher grade of epithelial remodeling was associated with higher YAP induced proliferation, leading to reduced ciliated cells and goblet cells. The finding was further verified using an IL-13 remodeling condition in differentiating ALI hNECs. Furthermore, YAP expression was positively correlated with proliferation and neutrophil infiltration in NIP. YAP expression was also significantly increased in NIP patients with adverse outcomes. Conclusion: Abnormal expression of YAP/active YAP is associated with proliferation, differentiation, neutrophil infiltration, and adverse outcome in NIP, and may present a novel target for diagnosis and intervention in NIP.